Sistem Penjamin Mutu Berbasis Rekognisi - Oktawira, Leni; Apriyenti, Apriyenti; Jamilus, Jamilus (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze a quality assurance system based on recognition within educational institutions. This research uses a literature study (library research) approach as a basis for analyzing the concept of a recognition-based quality assurance system. Literature sources were collected through national and international journal databases, such as Google Scholar, DOAJ, and other academic portals, with relevant publication ranges. The analysis was conducted using content analysis methods by examining the main ideas, reasoning flow, approaches, and findings from various literature sources. The analysis results indicate that the educational quality assurance system includes time management as a strategic aspect to ensure that the stages of planning, implementation, monitoring, and evaluation are carried out on time for the sustainability of education quality. A structured Internal Quality Assurance System allows for consistent and gradual quality improvement. The main challenges in quality assurance regulations include policy and implementation gaps, a weak quality culture, limited resources, and a lack of regulatory synchronization. Solutions to these issues include developing contextual operational guidelines, enhancing the capacity of the academic community, strengthening monitoring and evaluation, harmonizing regulations, and providing adequate resources to support the effective implementation of quality assurance.